The effect of task-based language teaching on Sri Lankan undergraduates speaking skills - Ithayaraj, Aloysius Britto (2021)
The present study attempts to test the effect of Task-Based Language Teaching (TBLT) to examine whether it has effectiveness in helping student to enhance their speaking skill. To this end , the present study designed with two-fold objectives. First, to investigate the effect of TBLT on speaking English among undergraduates in Sri Lanka. Second, to explore the attitudes of students towards TBLT and its usage to learn speaking skill.